Early Bronze Age settlement from ancient city Samshvilde - Shanshashvili, Nino; Narimanishvili, Goderdzi (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
A settlement of the Kura-Araxes culture was discovered on the territory of the ancient city of Samshvilde. Houses of the Early Bronze Age were excavated west of the Temple of Sioni of Samshvilde in of 50-70 m. The houses are damaged by pits and walls of the medieval era. The walls of the houses are so fragmented that the plan of housing is difficult to determine. In the northern part of the excavation site, only a small part of a stone wall and a shelf have survived. Both of these structures are built of basalt stones. The shelf was covered with a clay solution. On the shelf were placed grain grinders and mortars, flint inserts of a sickle, and ceramic vessels of various sizes. At the base of the shelf there was placed a rectangular slab, the surface of which was covered with intricate geometrical décor. At the base of the shelf there were also placed fragments of a large vessels and ceramics of various sizes. Almost all ceramics are richly ornamented with spiral and linear décor. A similar decor is typical for ceramics of the late stage of the Kura-Araxes culture of Kvemo Kartli, Armenia and Iran. The Early Bronze Age ceramics, which were discovered on the Samshvilde settlement belong to the late stage of the Kura-Araxes culture and dates back to the 28th-27th centuries. BC.